Self-regulated learning: Overview and potential future directions in geoscience. Issue 1 (8th October 2020) - Lukes, Laura A.; Jones, Jason P.; McConnell, David A.
Abstract: Self-regulated learning (SRL) models provide a framework for understanding the observed variance of student performance in geoscience learning contexts. Instructors can potentially use a SRL framework to support students in self-identifying the specific approaches to learning they use when engaging in geoscience learning situations (coursework, field experiences, visualization and abstraction tasks, etc.) and guide them in adopting more effective learning strategies and tactics, ultimately improving their performance and learning. Presented here is a summary of a SRL theoretical framework from the educational psychology community, an overview of recent research in science learning at the college-level using SRL frameworks, and recommendations for future SRL research directions in geoscience to promote SRL in teaching and learning practices.